2017
DOI: 10.3389/fpsyg.2017.00662
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Leitmotives in Richard Wagner's Der Ring des Nibelungen

Abstract: The music of Richard Wagner tends to generate very diverse judgments indicative of the complex relationship between listeners and the sophisticated musical structures in Wagner's music. This paper presents findings from two listening experiments using the music from Wagner's Der Ring des Nibelungen that explores musical as well as individual listener parameters to better understand how listeners are able to hear leitmotives, a compositional device closely associated with Wagner's music. Results confirm finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Recently the test has been modified and adapted using more sophisticated statistical modeling, resulting in shorter versions of the test, which reportedly have the same construct validity as the original (Harrison, Collins, & Müllensiefen, 2017). In its complete form, the Gold-MSI takes about 30 minutes to complete, although some researchers elect to only use relevant subcomponents such as solely the Musical Training sub-scale (Baker & Müllensiefen, 2017;Farrugia, Jakubowski, Cusack, & Stewart, 2015). The tool has proved especially useful in studies where it has been combined with other measures such as measures of personality (Greenberg et al, 2015) and socio-economic status (Müllensiefen et al, 2014), and has been used as a tool to measure aspects of development (Müllensiefen, Harrison, Caprini, & Fancourt, 2015).…”
mentioning
confidence: 99%
“…Recently the test has been modified and adapted using more sophisticated statistical modeling, resulting in shorter versions of the test, which reportedly have the same construct validity as the original (Harrison, Collins, & Müllensiefen, 2017). In its complete form, the Gold-MSI takes about 30 minutes to complete, although some researchers elect to only use relevant subcomponents such as solely the Musical Training sub-scale (Baker & Müllensiefen, 2017;Farrugia, Jakubowski, Cusack, & Stewart, 2015). The tool has proved especially useful in studies where it has been combined with other measures such as measures of personality (Greenberg et al, 2015) and socio-economic status (Müllensiefen et al, 2014), and has been used as a tool to measure aspects of development (Müllensiefen, Harrison, Caprini, & Fancourt, 2015).…”
mentioning
confidence: 99%
“…Features derived from the FANTASTIC toolbox have been successful in predicting a range of musical perception behavior (Baker & Müllensiefen, 2017;Harrison et al, 2017;Jakubowski et al, 2017;Kopiez & Müllensiefen, 2011) and thus serve as a useful metric from which PERCOREMA can be compared. In order to make this benchmark comparison, PECOREMA's performance is visualized against five features from the toolbox.…”
Section: Benchmarking With Fantasticmentioning
confidence: 99%
“…For example, there currently exists rationale for using computational measures to model aspects of musical cognition (Pearce, 2018) when memory is conceptualized as compressibility (Eerola et al, 2009) using information content frameworks. For example, Pearce and Müllensiefen found that measures of compressibility can be used as predictors of musical similarity (Pearce & Müllensiefen, 2017) and work using symbolic summary features has additionally been successful at modeling musical memory using computational measures of complexity (Baker & Müllensiefen, 2017; J. C. Bartlett & Dowling, 1980;Cuddy & Cohen, 1976;Cuddy & Lyons, 1981;Harrison et al, 2017).…”
Section: New Frameworkmentioning
confidence: 99%
“…For example, it would be difficult to attempt to change an estimation of tonalness by adding in non-diatonic notes to a melody without altering the pitch or interval entropy calculations. Some researchers have attempted to side-step this problem by using data reductive techniques such as principal component analysis in order to distill features from the melodic data to a single complexity score (Baker & Müllensiefen, 2017;Harrison et al, 2017), but given the degree of predictive ability from measures here related to information content, adding a data reductive model here might make things more difficult to interpret for future work.…”
Section: Previous Work Connectionsmentioning
confidence: 99%